A review for discovering bioactive minor saponins and biotransformative metabolites in Panax quinquefolius L. - Yang, Zhiyou; Deng, Jiahang; Liu, Mingxin; He, Chuantong; Feng, Xinyue; Liu, Shucheng; Wei, Shuai (Frontiers in Pharmacology, 2022)
Panax quinquefolius has attracted extensive attention worldwide because of the prominent biological functions on type 2 diabetes, cancers, central nervous system, and cardiovascular diseases investigated for decades. Active phytochemicals of Panax quinquefolius are ginsenosides, which can be classified as propanaxdiol (PPD)-type, propanaxtriol (PPT)-type, oleanane-type, and ocotillol-type oligo-glycosides depending on the skeleton of aglycone. Recently, advanced analytical and isolated methods including ultra-performance liquid chromatography tandem with mass detector, preparative high-performance liquid chromatography, high speed counter-current chromatography have been used to isolate and identify minor components in Panax quinquefolius, which accelerates the clarification of its material basis. Meanwhile, the poor bioavailability and undetermined bio-metabolism of most saponins has greatly hindered both the development of medicines and the identification of their real active constituents. Thus, it is essential to consider the bio-metabolism of constituents before and after absorption. In this review, we described the structures of minor ginsenosides in Panax quinquefolius, including naturally occurring protype compounds and their in vivo metabolites. The preclinical and clinical pharmacological studies of the ginsenosides in the past few years are also summarized. The review will promote the reacquaint of minor saponins on the growing appreciation of their biological role in Panax quinquefolius.